Food security and food quality among vanilla farmers in Madagascar: the role of contract farming and livestock keeping - Jessica Noromalala Andriamparany; Hendrik Hänke; Eva Schlecht (Food Security, 2021)
The northeastern SAVA region of Madagascar is the largest vanilla producing area in the world and is flourishing due to a large global demand for natural vanilla. Although the general socio-economic situation has regionally improved because of high vanilla prices, little is known about the nutritional status of local vanilla farmers. We used a 12-month longitudinal food survey to analyze food security, food consumption and nutrient intake of local vanilla farming households (n0.167em=0.167em140). Food consumption data was complemented with baseline, agro-economic, longitudinal and field-plot information to determine factors influencing food security, and the contribution of protein from Animal Source Food (ASF_protein) to household nutrition using a stepwise generalized linear model. Results show a high level (74%) of food insecurity and micronutrient deficiency but an acceptable level of protein intake among surveyed households. Consumption of rice, the principal source of carbohydrates, is stable across the year. Compared to other regions in Madagascar, local diets are moderately diversified with an acceptable share of ASF_protein (about 50%). Household size (P0.167em<0.167em0.001) and cash income from rice sales (P0.167em<0.167em0.001) were the most important factors influencing the food security index (FSI), while cash crop income (P0.167em<0.167em0.01) and number of income sources (P0.167em<0.167em0.01) were more important in the explanation of the dietary share of ASF_protein. Yet, neither livestock ownership nor contracting with vanilla buyers/exporters did improve food security of the surveyed households. Households who concluded contracts were significantly less food secure than non-contracting households (P0.167em=0.167em0.01) with seasonal fluctuations across the year. Policy implications of our findings are that, although many actors of the vanilla value chain run social and environmental programs in the SAVA region, more needs to be done to improve diet quality at household level and strengthen farmers' resilience to food insecurity.
Keywords: 630; Animal source food; Dietary diversity; Food security index; Seasonality; Vanilla farmers